Positive and negative emotions, L2 grit and perceived competence as predictors of L2 motivated behaviour - Pawlak, Mirosław; Zarrinabadi, Nourollah; Kruk, Mariusz (Journal of multilingual and multicultural development, 2024)
Relatively few studies in the field of second language acquisition have undertaken to investigate the interrelationships of constellations of individual difference variables. This is certainly true of how complexes of ID factors impact motivation to learn an additional language. In order to address this gap, the paper reports a study that examined the ways in which enjoyment, anxiety, boredom, L2 grit and self-perceived competence interact with each other and affect motivated learning behaviour in the case of 238 Iranian students majoring in English. The data were collected through an online questionnaire and, following confirmatory factor analysis, were subjected to path analysis. Among other things, the results showed that intended effort was the consequence of a complex interplay of factors, with the combined impact of these factors not always being obvious. It was also revealed that L2 motivation may in some circumstances be positively influenced by academic emotions that are generally considered to have a detrimental effect on L2 learning (i.e. anxiety, boredom).